Motivação e significados do trabalho: o caso dos metalúrgicos - Tamara Palmieri Peixoto (2014)
Metallurgy is a key sector for Brazilian economics. Moreover, its workers political engagement has resulted in considerable achievement for the countrys labor laws. Prior studies have investigated the connection between motivation and the meaning of work for a range of specific occupations. Nevertheless, no research is known to have been carried out with workplace relations found in the metallurgic. Focusing research particularly in certain occupations potentially contributes to drawing an understanding of how the aforementioned phenomena relate. Therefore, the present study has been conducted with the goal of identifying motivation and the meaning of work for the metallurgists of a medium-sized company located in Belo Horizonte (MG). In addition to that, it has aimed to delve into the connection established between those two concepts when specifically contextualized in the participants work environment. The Expectancy Theory of Motivation and a Meaning of Work multifaceted paradigm have guided the theoretical framework. Both have been adopted bearing in mind an analytical perspective committed to the socio-historical contextualization of phenomena. The following three strategies have been applied in the Methodological Triangulation: 1) Categorical Content Analysis technique, which has enabled documental research to be carried out in union newsletters, collective agreements and conventions (2009 to 2012), as well as in websites that feature the theme of metallurgical work; 2) Administering the following structured questionnaires: Socio-demographic, Work Centrality, Meaningful Work Inventory (MWI), and Measure of Work Motivation (MWM); And finally, 3) Semi-structured interviews. The aftermath of the first strategy has been a more accurate view of the metallurgists work environment, enabled by the contextualized analysis of their workplace relations. Moreover, its outcome has supported further hypotheses, which have been proposed in the assessment of the present phenomena. A convenience sampling of 110 metallurgists was interviewed for the second strategy. Finally, in the third strategy, a group of seven metallurgists were interviewed. Statistical analysis was carried out in order to analyze the connection between the aforementioned phenomena, for example: ANOVA, Cluster Analysis, Linear Regression Analysis (stepwise) by using the SPSS (Statistical Package for Social Science) software. The statistical assessment has been contrasted with both the interviews and the theoretical framework. As a result, moderate motivational strength has been identified. In regards to the meaning of work, it has been elicited that the descriptive type Challenge Oneself is the most prevalent in the daily routine of the metallurgists who partook this study. Additionally, the valuing type Expressing Respect and Support is the chief goal for those workers. The results have indicated a connection between motivation and the meaning of work. This highlighting the importance of the descriptive type Recognition and Facing Demands and Hardships, despite regression analysis having identified low explanatory power. The connections drawn may enlighten decisions regarding the organizational practices to be adopted in order to promote work motivation.